2019
DOI: 10.1007/s40534-019-00195-6
|View full text |Cite
|
Sign up to set email alerts
|

Data analytics approach for travel time reliability pattern analysis and prediction

Abstract: Travel time reliability (TTR) is an important measure which has been widely used to represent the traffic conditions on freeways. The objective of this study is to develop a systematic approach to analyzing TTR on roadway segments along a corridor. A case study is conducted to illustrate the TTR patterns using vehicle probe data collected on a freeway corridor in Charlotte, North Carolina. A number of influential factors are considered when analyzing TTR, which include, but are not limited to, time of day, day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…is research assumed that the traffic congestion occurs when the travel time is higher than twice the free-flow travel time. e free-flow speed of each route is obtained as the 85 th percentile speed during overnight hours (10 p.m. to 5 a.m.) [9,31,32]. Note that the free-flow travel time of each route is inversely proportional to free-flow speed; thus, the free-flow travel time is defined as the 15 th percentile travel time during overnight hours.…”
Section: Travel Time Reliability Measuresmentioning
confidence: 99%
“…is research assumed that the traffic congestion occurs when the travel time is higher than twice the free-flow travel time. e free-flow speed of each route is obtained as the 85 th percentile speed during overnight hours (10 p.m. to 5 a.m.) [9,31,32]. Note that the free-flow travel time of each route is inversely proportional to free-flow speed; thus, the free-flow travel time is defined as the 15 th percentile travel time during overnight hours.…”
Section: Travel Time Reliability Measuresmentioning
confidence: 99%
“…ey recommended using 95th percentile travel and buffer time as reliability indicators for bus routes [7]. Some recent route-based studies can be found in [8][9][10][11][12]. Because the focus of route-based studies is usually on one or a few specific routes, data were usually project-specific and most were discarded upon completion of a project, which makes continuous investigation difficult and sometimes impossible.…”
Section: Introductionmentioning
confidence: 99%
“…They also investigated the impact of incidents on travel times. Chen and Fan ( 9 ) provided a systematic approach to the analysis of TTR patterns from probe vehicles and from conducting a case study on a freeway they found clear variations in the days-of-week (DOW) and weather conditions. Yazici et al ( 5 ) analyzed differences in travel time and variability patterns between urban roads and highways based on taxi GPS and automatic vehicle location data.…”
mentioning
confidence: 99%
“…Using these data, the travel time index (TTI) is studied as an example of a TTR measure. TTI is preferred over other TTR measures such as the planning time index (PTI) used by Chen and Fan ( 9 ), because the average travel time used by the TTI is meaningful even for a lower number of observations in a sparse data setting and because it is easy to interpret. The average travel time’s disadvantage of changing over time ( 9 ) has not much influence in the setting of this study as it does not compare data of multiple years.…”
mentioning
confidence: 99%